STUDENT’S ATTITUDE ON CRITICAL LITERACY - BASED INSTRUCTION IN TEACHING WRITING IN EFL CLASSROOM - Ahmad Arkam Ramadhani (JURNAL KONFIKS, 2022)
The study investigates the student’s attitude toward critical literacy-based instruction in teaching writing in EFL university classrooms it employs a descriptive study using a purposive sampling technique and takes 30 respondents from EFL university students. The questionnaire and interview were used to collect data on the perception of EFL university Students on critical literacy-based instruction in the process of learning and observation was applied to gain data on the EFL Students’ interaction with critical Literacy based Instruction in teaching critical literacy in teaching writing in EFL classroom fall into 3 categories: (1) highly understanding of Critical Literacy (HUCL): (2) moderately understanding of Critical Literacy (MUCL) (3) low understanding of Critical literacy (LUCL). This research is expected to be beneficial for lecturers, students, and stakeholders to enrich knowledge and develop language skills and proficiency based on critical literacy instruction to teach writing in EFL classrooms. This research is to be a reference for teacher professional development, especially teacher capacity teaching writing EFL classrooms.